Adopting Ecodesign Management Systems in the construction sector. Analysis from the perspective of stakeholders (2016)
In order to analyze the main reasons, the adoption process, outcomes and satisfaction obtained by the architecture firms and other actors involved in the process of adopting the ISO 14006 eco-design standard, we developed a qualitative research using a Delphi type methodology, based on the results of a previous multiple case study research conducted with nine architecture firms. Among the main results, it should be highlighted the difficulties faced by architecture firms to obtain environmental information of raw materials, the poor recognition given by the client to environmental aspects compared with costs and the limited role of government supporting eco-design adoption, increasing the level of requirements of environmental legislation, and taking into account environmental issues in public tenders. It is also noteworthy the main stakeholders involved in the adoption and certification process of the ISO 14006 have demonstrated a medium or medium-high level of satisfaction.